A Systemic Functional Matrix of Chinese Phonology. (10th December 2015) - Yali, Ou; Chengyu, Liu
Abstract : This paper looks at the Chinese phonological system from within a Systemic Functional framework. It discusses such prosodic features as r-ization, stress, segmental lengthening and shortening, rhyming and tone accordance. These work for the hierarchically ranked units of syllable (initial and final), prosodic word (PW: standard PW, super PW and degenerate foot), prosodic phrase and intonational group on the one hand, across the diversified systems of ideational, interpersonal and textual functions on the other. The two dimensions hence constitute a systemic-functional matrix, with the system as the basis and the function as the motive.